C programming for microcontrollers : featuring ATMEL's AVR Butterfly and the free WinAVR compiler. - Pardue, Joe, ....- (Knoxville : Smiley Micros, 2005)
Do you want a low cost way to learn C programming for microcontrollers? This book shows you how to use Atmel's $19.99 AVR Butterfly board and the FREE WinAVR C compiler to make a very inexpensive system for using C to develop microcontroller projects. Students will find the thorough coverage of C explained in the context of microcontrollers to be an invaluable learning aide. Professionals, even those who already know C, will find many useful tested software and hardware examples that will speed their development work. In addition to an in-depth coverage of C, the book has projects for: Port I/O reading switches and blinking LEDs UART communication with a PC Using interrupts, timers, and counters Pulse Width Modulation for LED brightness and motor speed control Creating a Real Time Clock Making music ADC: Analog to Digital Conversion DAC: Digital to Analog Conversion Voltage, light, and temperature measurement Making a slow Function Generator and Digital Oscilloscope LCD programming Writing a Finite State Machine CD contains all the source code, the free WinAVR C compiler, AVRStudio, and lots of other useful things.
Keywords: Microcontrollers; Programmeren